Answers

  • Brainly User
2014-09-24T13:10:03+05:30
Important formulas:-
(a + b)² + (a - b)² = 2a² + 2b²
(a + b)² -  (a - b)² = 4ab

Above formulas should be remembered . Also should confirm above result by expanding (a + b)² and (a - b)² and simplifying. This will be an aid to memorise also as you will know how these results are obtained.
-----------------------------------------------------
Now to the question.
you have to find, (x + 1)² - (x - 1)²
If you compare with the above formulas , see that a = x and b = 1,
Hence from second formula, (x + 1)² - (x - 1)² =  4.x.1 = 4x = 4(2 - √3) = 8 - 4√3
0
2014-09-24T14:19:27+05:30
X=2-√3
so,x+1=2-√3+1
=3-√3
so,(x+1)²=(3-√3)²
By using the identity (a-b)²=a²-2ab+b²,we get
(3-√3)²=3²-2*3*√3+(√3)²
=9-6√3+3
=12-6√3
=6(2-√3) (FOUND SAME AS 6x)
ANS=6(2-√3)
0
OOPS!I MISREAD THE QUESTION PLZ DELETE IT
How to get mathamatical keyboard in iPad mini